Progress, challenges and opportunities in early modern gender history, c.1550–1720. Issue 170 (November 2022) - Tait, Clodagh
Abstract: Following some of the themes of the original 'An agenda for women's history in Ireland, 1500–1900' and others that were not as prominent, this article considers progress since 1992 and highlights opportunities for the further development of Irish early modern women's and gender history. It considers aspects of the life cycle of women and men, especially birth, youth and marriage; the economic roles of women, especially when it came to work and property; and the importance of movement to and from Ireland in both personal biographies and wider contexts. It also reflects on some of the ways in which understandings of early modern politics and of religion and belief for the period c .1550–1720 have been transformed by consideration of the role of women. While the 'Agenda' noted the potential of buildings and spaces, there has been a new emphasis on 'things' as remnants of lives and labour, expressions of cultural norms and tools in the construction of gender, selfhood and social status. Very early on, the 'Agenda' strongly stated that 'the history of women is also the history of men', and this article also notes the green shoots of the history of masculinity in early modern Ireland.